Quality of Life and Waterborne Diseases: the invisibility of Schistosomiasis mansoni in the tourist towns of Chapada Diamantina, Bahia State, Brazil (Research, Society and Development, 2020)
Waterborne Diseases (DVH’s) are a constant threat to quality of life. Among them, Schistosomiasis mansoni (MS) is one of the most common to manifest in man. In 2017, 944 cases of the disease were registered in Lençóis, in Chapada Diamantina, but only after the contamination of a group of tourists from Minas Gerais, the public's attention turned to this reality. Thus, this research aimed to investigate what is the prevalence of MS in touristic municipalities in the region and how the disease has been approached as established by the Ministry of Health. This is a qualitative study that used bibliographic and documentary research as methodological procedures, in addition to conducting semi-structured interviews. It was identified that there are no notifications about the cases of the disease and the actions to cope with it are developed in a heterogeneous manner in the municipalities, being influenced by administrative, economic and political issues. The interference of these factors weakens the success of the activities for the management of Schistosomiasis mansoni and, consequently, compromises the quality of life of its inhabitants. In order to improve the scenario, better planning of actions and distribution of resources for strategies to combat the disease in these municipalities is necessary.